Drug-Induced Arrhythmias: A Scientific Statement From the American Heart Association. Issue 15 (13th October 2020) - Tisdale, James E.; Chung, Mina K.; Campbell, Kristen B.; Hammadah, Muhammad; Joglar, Jose A.; Leclerc, Jacinthe; Rajagopalan, Bharath
Abstract : Many widely used medications may cause or exacerbate a variety of arrhythmias. Numerous antiarrhythmic agents, antimicrobial drugs, psychotropic medications, and methadone, as well as a growing list of drugs from other therapeutic classes (neurological drugs, anticancer agents, and many others), can prolong the QT interval and provoke torsades de pointes. Perhaps less familiar to clinicians is the fact that drugs can also trigger other arrhythmias, including bradyarrhythmias, atrial fibrillation/atrial flutter, atrial tachycardia, atrioventricular nodal reentrant tachycardia, monomorphic ventricular tachycardia, and Brugada syndrome. Some drug-induced arrhythmias (bradyarrhythmias, atrial tachycardia, atrioventricular node reentrant tachycardia) are significant predominantly because of their symptoms; others (monomorphic ventricular tachycardia, Brugada syndrome, torsades de pointes) may result in serious consequences, including sudden cardiac death. Mechanisms of arrhythmias are well known for some medications but, in other instances, remain poorly understood. For some drug-induced arrhythmias, particularly torsades de pointes, risk factors are well defined. Modification of risk factors, when possible, is important for prevention and risk reduction. In patients with nonmodifiable risk factors who require a potentially arrhythmia-inducing drug, enhanced electrocardiographic and other monitoring strategies may be beneficial for early detection and treatment. Management of drug-induced arrhythmias includes discontinuation of the offending medication and following treatment guidelines for the specific arrhythmia. In overdose situations, targeted detoxification strategies may be needed. Awareness of drugs that may cause arrhythmias and knowledge of distinct arrhythmias that may be drug-induced are essential for clinicians. Consideration of the possibility that a patient's arrythmia could be drug-induced is important. Abstract : Supplemental Digital Content is available in the text.